Does stroke rate determine swimming velocities values and coordination? - Potdevin, F.; Pelayo, P.; Delignieres, D. (Biomechanics and Medicine in Swimming, Swimming Science IX, 2003)
The purpose of this study was to assess the effects of stroke rate (SR) on the reproducibility of swimming velocity (V) and index of coordination (IdC) values in a front crawl swimming sequence. The procedure was twofold. In the first procedure, 30 expert and non expert subjects performed two tests of 4 x 12.5-m. In the first test, they were requested to swim at a spontaneous low, average, fast and maximal speed. V and SR were measured. In the second test, SR was imposed at the values registered previously and V was compared with previous V values. Results showed equality between V values whatever the test step and the higher the SR values, the lower the difference in V values between the two test conditions. The results were similar in experts and non experts. In the second procedure, 9 expert swimmers performed two front crawl tests of 4 x 12.5-m. In each test, they were requested to swim the fastest with a SR set at 20, 30, 40, 50 cycles.min-1. IdC was calculated and compared for the same SR.. Results showed equality between IdC only when SR was higher than 40 cycles.min-1. We concluded of the intensities control and skills stabilisation by the SR for the swimming coachs. We suggested that coordination could be explain by dynamic concepts. Key words : Stroke rate, Velocity, Index of Coordination.